Chemical composition and biological properties of Pelargonium graveolens, Leptospermum petersonii and Cymbopogon martinii var. motia essential oils and of Rosa centifolia absolute - Nikolić, Miloš (2021)
Chemical composition of the essential oils (EO) of Pelargonium graveolens, Leptospermum petersonii and Cymbopogon martinii var. motia, and the absolute of Rosa centifolia and their bioactivity were examined. Major compounds in P. graveolens EO were monoterpene alcohols citronellol, geraniol and linalool; in L. petersonii EO monoterpene aldehydes geranial, neral and citronellal; in C. martiniii var. motia EO monoterpene alcohol geraniol and ester geranyl acetate, while in absolute of R. centifolia aromatic alcohol 2-phenylethanol. The EO of L. petersonii showed the strongest antibacterial while the EO of C. martinii var. motia the strongest antifungal potential. The best biofilm inhibition capacity was observed with R. centifolia absolute. The results of scanning electron microscopy analysis indicated that the EOs of L. petersonii and P. graveolens changed the number and morphology of C. albicans cells. The L. petersonii EO was the most potent toward tumour cells and exhibited the best biological activity. This is first comparative report summarizing efficacy of studied aromatic samples against pathogenic microbes, providing deeper insight into the modes of antimicrobial action, and at the same time describing their cytotoxicity against cell lines.